A Review of the Longstanding Ban on Private Supplementary Tutoring in Tanzania Mainland - Anangisye, William A. L. (Papers in Education and Development, 2018)
Schools in general and private supplementary tutoring programmes in particular have both been concerned with the provision of basic education. The two can complement each other when effectively put into practice. However, in Tanzania Mainland private supplementary tutoring has remained banned. This paper revisits this ban, questioning why private supplementary tutoring has been banned on Tanzania Mainland when education is a basic right. It argues that, unless the forces which fuelled the dire need for private supplementary tutoring among pupils and teachers are adequately addressed, attempts to ban this practice will be futile since it continues to operate unabated largely underground or under the noses of the authorities. Moreover, the paper advocates for a clearer rationale for private supplementary tutoring as an alternative approach to poor quality education in Tanzania. Keywords: ban; private tutoring; Tanzania Mainland; primary school; secondary school